Electron Tomography: Quantitative Structure Determination of Large Three‐Dimensional Nanoparticle Assemblies (Part. Part. Syst. Charact. 1/2013). (7th November 2012) - Altantzis, Thomas; Goris, Bart; Sánchez‐Iglesias, Ana; Grzelczak, Marek; Liz‐Marzán, Luis M.; Bals, Sara
<x xml:space="preserve">Abstract</x> Electron tomography is an important tool to investigate nanoassemblies in three dimensions. As reported by Sara Bals and co‐workers on page 84, the complete electron tomography approach is optimized to quantify the number of particles in the assembly. The image shows a 3D reconstruction of a spherical self‐assembly of gold nanoparticles. The background consists of false‐colored 2D projection images that are used for the reconstruction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>